Mathematical Modeling of Termophysical Processes Attending Multilayer System Self-Propagating High-Temperature Synthesis Welding; Zel'dovich Memorial; Vol. 2 - Aligozhina K. A. Kamila Abaevna (2015, 2015)
В фонде НТБ ТПУ отсутствует